Analysis on Stress Control Technology of Long Span Continuous Beam Casting - Yu, Guoquan (Journal of Theory and Practice of Engineering Science, 2023)
Along with our country urbanization process unceasingly speeds up, the highway and railway transportation is becoming more and more important, but because in the construction process, the construction environment is more complex, the construction condition is poorer, environmental protection aspect's requirement is higher, causes our country highway and bridge construction to become very slow, Therefore, relevant departments need to actively use the large-span continuous beam cantilever pouring construction stress control technology, so as to ensure that the bridge can meet the design of internal forces, the use of stress control technology and the use of linear control during construction. Taking the Zheng-Wan high-speed railway project as an example, relevant personnel need to explore how to use the large-span continuous beam cantilever casting construction stress control technology in the construction process, and how to control, how to choose the test tools, and how to arrange reasonable measuring points, so that the structural stress is kept in a stable range, so as to ensure the safety of the bridge and stability performance.